1989
DOI: 10.1901/jaba.1989.22-417
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Procedural Components of Supported Employment Programs Associated With Employment Outcomes

Abstract: This study examined the relation between the procedural components of supported employment programs and employment outcomes for 120 individuals with disabilities. These individuals were involved in supported employment programs established through the Utah Supported Employment Project. The results suggest that successful implementation of supported employment services led to ongoing employment of study participants in community work sites, increased wages, and ongoing opportunities for workers to interact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 4 publications
1
18
2
Order By: Relevance
“…This is in contrast to the findings of McDonnell, Nops, Hardman, and Chambles ( 1989), who found that level of mental retardation was associated with supported employment outcomes. However, their outcome measure was average weekly wage.…”
Section: Integration Of Results With Existing Researchcontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the findings of McDonnell, Nops, Hardman, and Chambles ( 1989), who found that level of mental retardation was associated with supported employment outcomes. However, their outcome measure was average weekly wage.…”
Section: Integration Of Results With Existing Researchcontrasting
confidence: 99%
“…This finding ap, peared to be consistent with the results reported by Botuck, Levy, Kramer, Levy, and Rimmerman ( 1992 ), Levy et al ( 1994), McDonnell et al ( 1989, and Ward, Dowrick, and Weyland (1993).…”
Section: Integration Of Results With Existing Researchsupporting
confidence: 91%
“…Even the most justifiable modifications, those sensitive to gender, race and ethnicity, do not consistently alter or sustain practice effectiveness (Gottfredson and Koper 1996;Botvin et al 1995Botvin et al , 2001. Conversely, mental health services research shows a positive relationship between model fidelity and implementation effectiveness (e.g., Jerrel and Ridgely 1999;McDonnell et al 1989;McHugo et al 1999). Prevention research also indicates that effectiveness decreases with erosion of the model over time, but not with adaptations in the form of additions (Battistich et al 1996;CSAP 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, programs that are higher in fidelity will have better outcomes. This hypothesis has been examined in a wide range of practices, with generally moderate to strong support for the fidelityÀoutcome relationship (e.g., Blakely et al, 1987;Henggeler, Pickrel, & Brondino, 1999;Jerrell & Ridgely, 1999;McDonnell, Nofs, Hardman, & Chambless, 1989;Oxman et al, 2006). This hypothesis has been extensively examined for two of the practices implemented in the current project, that is, SE (Becker, Smith, Tanzman, Drake, & Tremblay, 2001;Becker, Xie, McHugo, Halliday, & Martinez, 2006;McGrew & Griss, 2005;McGrew, 2007) and ACT (Bond & Salyers, 2004;Latimer, 1999;McGrew, Bond, Dietzen, & Salyers, 1994;McHugo, Drake, Teague, & Xie, 1999).…”
Section: The National Ebp Projectmentioning
confidence: 99%